2003
DOI: 10.1210/jc.2003-030971
|View full text |Cite
|
Sign up to set email alerts
|

No Increase of Blocking Type Anti-Thyrotropin Receptor Antibodies During Pregnancy in Patients with Graves’ Disease

Abstract: Serial changes in serum levels of anti-TSH receptor antibodies were examined during and after pregnancy in six patients with Graves' disease receiving no or minimal maintenance doses of antithyroid drugs. During pregnancy, serum levels of TSH-binding inhibitory Igs (P < 0.001) and thyroid-stimulating antibodies (TSAbs) (P < 0.01) decreased gradually but increased after delivery in all patients. Activities of thyroidstimulation blocking antibodies (TSBAbs) were lower than the cut-off value in early pregnancy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 23 publications
1
27
1
1
Order By: Relevance
“…This threshold value was provided by a mother who relapsed with GD late in pregnancy, and for whom no TBII determination had been made before T3. TBII values generally decrease during pregnancy (10,28), as was observed for most of our patients. Therefore, it could be argued that our threshold value, derived from a TBII determination at T3, is underestimated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This threshold value was provided by a mother who relapsed with GD late in pregnancy, and for whom no TBII determination had been made before T3. TBII values generally decrease during pregnancy (10,28), as was observed for most of our patients. Therefore, it could be argued that our threshold value, derived from a TBII determination at T3, is underestimated.…”
Section: Discussionsupporting
confidence: 86%
“…Individual cases are shown in Table 2. The median age of the women at the beginning of pregnancy was 31 years (range, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Twenty mothers of 21 neonates (one twin pregnancy) had a past history of GD.…”
Section: Clinical Characteristics Of the Mothersmentioning
confidence: 99%
“…In most instances, pregnancy is associated with a progressive decrease in the autoimmune activity of Graves' disease (13,14), so that in women receiving antithyroid medication for Graves' hyperthyroidism before becoming pregnant it is often feasible to gradually reduce the dose or to withdraw the medication (14,15). Occasionally, as reported in a few studies (16,17), but not confirmed on a large scale (18), the nature of TRAb may change during pregnancy from stimulation to blocking of the TSH receptor. In such patients not only withdrawal of antithyroid medication, but also therapy of the mother with L-T 4 may be necessary.…”
Section: Graves' Disease and Pregnancy In Various Combinationsmentioning
confidence: 99%
“…Several studies reported that the serum TRAb values usually decreased during pregnancy [3,[15][16][17]. As a possible mechanism of this, Amino et al suggested that Th2-dependent humoral immunity is suppressed in human pregnancy [16].…”
Section: Disclosurementioning
confidence: 99%
“…As a possible mechanism of this, Amino et al suggested that Th2-dependent humoral immunity is suppressed in human pregnancy [16]. However, in some cases including those after radioiodine therapy, the high serum TRAb values might not decrease during pregnancy, resulting in fetal hyperthyroidism [18,19].…”
Section: Disclosurementioning
confidence: 99%